Physical health and cognitive ability factors in predicting retirement adjustment based on machine learning approach: results from the China Health and Retirement Longitudinal Study - Chenhong Cui; Bolin Zhou; Lin Gao; Dahua Wang; Angela C. Rowe; Bruna S. Nascimento; Hao Zhang; Xiancai Cao; Xiancai Cao; Xiancai Cao (Frontiers in Psychology)
IntroductionRetirement is one of the most significant status changes in an individual's later life. Physical health and cognitive ability are key predictors of retirement adjustment. However, studies have yet to investigate the role of different physical health and cognitive ability indicators simultaneously, and their non-linear association in relation to retirement adjustment.MethodsThis study used machine learning methods to explore the predictive role of both physical and cognitive ability variables in retirement adjustment. Using longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) database, a total of 1,314 participants met the retirement criteria, and the increase in life satisfaction and decrease in depression scores were extracted as the indicators of successful retirement adjustment. Various physical health and cognitive ability-related variables measured before retirement, alongside key demographic and lifestyle variables, were used as predictive variables to predict retirement adjustment 2 or 3 years later. Random forest (RF) and XGBoost classification models were used as predictors, and SHAP (SHapley Additive explanation) value analysis was used to explain the model prediction results.ResultsThe results indicated that the accuracy of the RF and XGBoost models outperformed regularized logistic regression. Self-rated hearing, income, attention and calculation ability, self-rated health, and time orientation ability were identified as the most influential predictors of retirement adjustment. Self-rated memory and sleep duration exhibited a non-linear relationship with retirement adjustment.DiscussionThe present research extends current understanding of factors that promote adjustment to retirement and provides essential insights for preventing poor adjustment and intervening in retirement adjustment.